Partnering for Water in Cote d'Ivoire : Lessons from 50 Years of Successful Private Operation - Marin, Philippe; Ouayoro, Eustache; Fall, Matar; Verspyck, Richard (World Bank, Washington, DC, 2012)
The public-private partnership (PPP) for the national water utility of Cote d'Ivoire is the oldest and largest water PPP in the developing world. In place since 1960 and today serving more than 7 million people, this PPP has provided quality service for decades and made remarkable progress in expanding access in the 1990s. It even proved resilient to civil strife and the de facto partition of the country in 2002. This African success story shows that a pragmatic partnership between a committed government and an efficient private operator can produce tangible and sustained benefits for the population.